KONSEP CYBERBULLYING DALAM PERSPEKTIF HUKUM PIDANA - Hariyanto Hariyanto (LPPM Universitas Ekasakti Padang, 2021)
This research is a normative legal research that aims to analyze the modus operandi of cyberbullying and analyze cyberbullying in the perspective of criminal law in Indonesia and other countries. The method in this study is a normative research method. The results of the study analyzed that the modus operandi of cyberbullying is various forms of bullying or bullying that is carried out through the internet. The modus operandi can be categorized into exclusion; flaming; impersonation/fake profiles; trickery; fraping; dissing; and cyberstalking. In Indonesia, cyberbullying is still not specifically regulated or limited. So the handling still depends on Law Number 19 of 2016 concerning Electronic Information and Transactions. Likewise in the Criminal Code the crime of cyberbullying is only limited to insults and defamation. An adequate discussion regarding cyberbullying is contained in Arkanas Regulation (AR Code) AR Code 5-71-217 (2015) in points (b), (c) and (d) as well as in the EU's Criminal Law in Conclusion of the Council 2009/C62 /05 of 27 November 2008 and the 2011/92/EU Directive on combating inappropriate treatment in cyberspace. This research is a normative legal research that aims to analyze the modus operandi of cyberbullying and analyze cyberbullying in the perspective of criminal law in Indonesia and other countries. The method in this study is a normative research method. The results of the study analyzed that the modus operandi of cyberbullying is various forms of bullying or bullying that is carried out through the internet. The modus operandi can be categorized into exclusion; flaming; impersonation/fake profiles; trickery; fraping; dissing; and cyberstalking. In Indonesia, cyberbullying is still not specifically regulated or limited. So the handling still depends on Law Number 19 of 2016 concerning Electronic Information and Transactions. Likewise in the Criminal Code the crime of cyberbullying is only limited to insults and defamation. An adequate discussion regarding cyberbullying is contained in Arkanas Regulation (AR Code) AR Code 5-71-217 (2015) in points (b), (c) and (d) as well as in the EU's Criminal Law in Conclusion of the Council 2009/C62 /05 of 27 November 2008 and the 2011/92/EU Directive on combating inappropriate treatment in cyberspace.